„Cukrovar v Gorne Orechovici se svými pobočnými závody činí dojem samostatné osady, jest částí výstavného města a závody samy jakousi stálou výstavou českého průmyslu“ - Jakoubek, Marek (Lidé města, 2024)
This contribution aims to describe the history of the Czech sugar factory in Gorna Oryahovitsa in Bulgaria. It presents the annotated transcript of an archival document written by one of the company’s high-ranking employees in the early 1930’s. The document contains comprehensive information about both the establishment of the sugar factory and its later development and operations. Thanks to this document, this contribution serves as a first introduction to the phenomenon of the largest sugar factory in the Balkans in its day, serving as a springboard for further study. The transcription is preceded by a short introduction into (the study of) the history of the Czech Gorna Oryahovitsa’s compatriot community, accompanied by a review of existing literature related to the topic.